2007
DOI: 10.1016/j.socscimed.2006.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Daily negative interactions and mood among patients and partners dealing with multiple sclerosis (MS): The moderating effects of emotional support

Abstract: Negative interactions with intimate partners may have adverse consequences for well-being, especially for individuals dealing with chronic illness. However, it is not clear whether negative interactions affect both dimensions of positive and negative well-being and factors that may moderate this effect have not been well-described. The aim of the present study was to examine the association between daily received negative responses from the partner and end-of-day positive and negative mood in patients with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…The role of social support in predicting psychological outcomes in populations living with MS has also been investigated. Support has been found for the impact of negative and positive social support on stress level, specifically, negative partner support served to increase perceived stress, but positive partner support reduced the detrimental impact of this negative social support on stress (Kleiboer, et al, 2007). Negative forms of partner social support have also been associated with increased disability, and worse physical and mental health among those with MS (Schwartz & Kraft, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of social support in predicting psychological outcomes in populations living with MS has also been investigated. Support has been found for the impact of negative and positive social support on stress level, specifically, negative partner support served to increase perceived stress, but positive partner support reduced the detrimental impact of this negative social support on stress (Kleiboer, et al, 2007). Negative forms of partner social support have also been associated with increased disability, and worse physical and mental health among those with MS (Schwartz & Kraft, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, social support has been conceptualized as representing two separate dimensions in previous research (i.e., Mavandadi, Rook, & Newsom, 2007). Indeed, past research underscores that negative and positive forms of social support are not just opposite ends of the same dimension (see for example, Kleiboer et al, 2007). Research on older community-dwelling adults found that positive social support (e.g., encouragement) predicted less future disability (as measured by perceived difficulty in performing activities of daily living) while negative social support (e.g., criticism) led to more future disability (Mavandadi et al, 2007).…”
Section: Positive and Negative Social Supportmentioning
confidence: 99%
“…The findings were echoed in a sample of people with multiple sclerosis who experienced more end-of-day negative mood when their spouses made disapproving remarks or were avoidant or demanding. However, the association between negative spouse behaviors and mood was weakened on days of high emotional support [70].…”
Section: Spouse Behavior and Experiences At Workmentioning
confidence: 99%
“…Spouses’ end‐of‐day mood benefited from giving instrumental support to and receiving emotional support from the PwMS (40). More daily hassles and higher end‐of‐day negative mood were reported by spouses who received negative responses from the PwMS than those who did not receive negative responses (41). However, the adverse effects of the received negative responses on end‐of‐day mood were moderated by receiving emotional support on the same day (41).…”
mentioning
confidence: 99%